Conhecimento botânico local e distribuição de cactaceae no Semiárido da Paraíba (Nordeste do Brasil) - Carvalho, Thamires Kelly Nunes (2016)
The semi-arid region is among the most populated regions of the country. Here, traditional populations interrelate with the surrounding plant resources. Among these the Cactaceae family includes enhanced by its strong presence and distribution throughout Caatinga also for its use and socio-cultural importance. In periods of drought, the need for the use of some species can carry this seasonal practice to larger consequences as influences the distribution, considering the climate outlook for the region. Thus, this work will be presented in the form of chapters, where the first is entitled BOTANICAL LOCAL KNOWLEDGE AND CACTACEAE USE IN SEMIARID OF PARAÍBA, NORTHEAST BRAZIL and aims to record and analyze the knowledge and use of farmers in a community rural Paraiba Curimataú have / do about the species Cactaceae present in the region; and second, DISTRIBUTION AND MODELING Cereus jamacaru DC. subsp. jamacaru and Pilosocereus pachycladus F. Ritter. subsp. pernambucoensis (F. Ritter) Zappi (CACTACEAE), FORAGE: FUTURES PERSPECTIVES, which aims to assess the current and future distribution of Cereus jamacaru DC. subsp. jamacaru and Pilosocereus pachycladus F. Ritter. subsp. pernambucoensis considering the dynamics of feed use due to climate changes. Both chapters were written independently, for their publication in different journals.